2016
DOI: 10.1299/jamdsm.2016jamdsm0013
|View full text |Cite
|
Sign up to set email alerts
|

Ankle joint pushing mechanism by stabilization of ankle position using a brace structure

Abstract: In the present study, a human ankle joint pushing mechanism with a brace structure was developed, and the force balance relationship of the proposed system to avoid pain at sites other than the ankle joint was evaluated. The proposed system uses the brace structure to prevent the movement of the geometric arrangement of the ankle joint and the device rotational axis when pressure is applied to the foot. The results of experiments revealed that the proposed brace mechanism did not change the position of the ank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…An automated foot-stretching device had been studied for use in the bed-side; it is suggested that robot-assisted passive stretching and active movement training effectively improve motor function and mobility for post-stroke patients and children with acute brain injury 8 , 9 , 10 , 11 , 12 , 13 ) . Toda et al created a foot-stretching machine that simulates a therapist pulling the heel and dorsiflexing the foot in a sitting position 14 , 15 ) . Their machine had one degree of freedom of motion for dorsi- and plantar flexion.…”
Section: Introductionmentioning
confidence: 99%
“…An automated foot-stretching device had been studied for use in the bed-side; it is suggested that robot-assisted passive stretching and active movement training effectively improve motor function and mobility for post-stroke patients and children with acute brain injury 8 , 9 , 10 , 11 , 12 , 13 ) . Toda et al created a foot-stretching machine that simulates a therapist pulling the heel and dorsiflexing the foot in a sitting position 14 , 15 ) . Their machine had one degree of freedom of motion for dorsi- and plantar flexion.…”
Section: Introductionmentioning
confidence: 99%
“…Yuma SHIRAISHI*, Shogo OKAMOTO*, Naomi YAMADA* , **, Koki INOUE*, Yasuhiro AKIYAMA* and Yoji YAMADA* Thus far, a few ankle stretching machines have been developed for treating or preventing ankle plantarflexion contractures. Machines for ankle dorsiflexion were developed using electromagnetic or linear motors (Waldman et al, 2013;Ren et al, 2017;Toda et al, 2016Toda et al, , 2019Zhou et al, 2016). Yamada et al developed a machine for 3D foot motion for dorsiflexion, abduction, and eversion using McKibben-type pneumatic actuators and wire-driven mechanisms Kimura et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…To realize the mechanization, though it is necessary to guarantee the subject safety, there is a possibility that the device malfunctions due to a human error such as a mistake in an operation of the patient or a system error due to a failure of the machine controller devices [6]. Since these errors occur accidentally, the patient's risk avoidance behavior was delayed, and the patient was injured ( Fig.…”
Section: Introductionmentioning
confidence: 99%